Short communication. Irrigation temperature effects on seedling growth and transplant quality of tomato, pepper and eggplant - Kadri Bozokalfa, M.
(Es, En)
Ilus., 19 ref.
Keywords: CAPSICUM ANNUUM; LYCOPERSICON ESCULENTUM; SOLANUM MELONGENA; TEMPERATURA DE AGUA; AGUA DE RIEGO; CRECIMIENTO; PLANTULAS; ESPAÑA